2017
DOI: 10.1021/acs.jced.6b00800
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation for Solubilities of Adipic Acid, Glutaric Acid and Succinic Acid in Acetic Acid + Cyclohexanone Mixtures

Abstract: Under atmospheric pressure, the solubilities of adipic acid, glutaric acid, and succinic acid in acetic acid + cyclohexanone mixtures were measured respectively by using the laser dynamic method in which the temperature ranged from 298.55 to 340.85 K and the mass fraction of cyclohexanone in the binary solvent mixtures ranged from 0.0 to 1.0. The results showed that the solubilities of adipic acid, glutaric acid, and succinic acid in acetic acid + cyclohexanone solvent mixtures all increased with decreasing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
(167 reference statements)
10
25
0
Order By: Relevance
“…The experimental apparatus and experimenting methods used in this work were described in detail by Luo. , Briefly, the dynamic detection method was applied to measure the solubility by a laser monitoring observation technique. The experimental apparatus are shown in Figure , which include laser-detecting equipment, a temperature-controlling and monitoring equipment, a solid–liquid equilibrium (SLE) vessel, and a magnetic stirrer. In brief, the experiment was performed in a jacketed equilibrium glass bottle with a reaction vessel of 100 mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental apparatus and experimenting methods used in this work were described in detail by Luo. , Briefly, the dynamic detection method was applied to measure the solubility by a laser monitoring observation technique. The experimental apparatus are shown in Figure , which include laser-detecting equipment, a temperature-controlling and monitoring equipment, a solid–liquid equilibrium (SLE) vessel, and a magnetic stirrer. In brief, the experiment was performed in a jacketed equilibrium glass bottle with a reaction vessel of 100 mL.…”
Section: Methodsmentioning
confidence: 99%
“…Song measured the solubilities of SA in acetic acid + water mixtures at the temperature range of 303.2–333.2 K and acetic acid + cyclohexane mixtures at the temperature range of 303.2–343.2 K . Luo measured the solubilities of AA, GA, and SA in acetic acid + cyclohexanone mixtures at the temperature range of 298.55–340.85 K …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of sodium chloride in subcritical water was determined using a flow-type measuring apparatus. This apparatus was designed and produced based on the work of Higashi et al and Leusbrock et al ,,, The schematic diagram of the apparatus is shown in Figure . In the apparatus, a high temperature and pressure equilibrium cell was produced by Hastelloy C-276 to prevent severe corrosion to the cell body.…”
Section: Methodsmentioning
confidence: 99%
“…The Flory–Huggins model is a strict theoretical model which is based on two traditional solution theories. These models have been successfully applied in correlating the solubilties of several inorganic salts in supercritical water with the range of data available. ,,, In contrast, other models are purely empirical models which do not have any thermodynamic theoretical background. In that case, the prediction of an empirical model over a wide range is less reliable than that of theoretical solubility model.…”
Section: Theoretical Empirical and Semiempirical Modelmentioning
confidence: 99%